Cloning of Lab Gene Encoding Bacteriocin From Pediococcus acidilactici Fil Into Escherichia coli DH5a - Sebastian Margono; Agus Wijaya; Endang S. Rahayu (agriTECH, 1998)
Pediococcus acidilactici F11 is able to inhibit the growth of related species of enterobacteriaceae by secreting bacteriocin. Effort to increase bacteriocin production by transforming lab gene encoding bacteriocin from P. acidilactici Fl 1 into E. colt DH5a was carried out. Plasmid pPAF11 (encoding bacteriocin from P. acidilactici F11) and p13C19 as vector which were double-digested with Madill and BamHI, ligated, and transformed into E. colt DH5a. White colonies, as indicator of transformant, were picked up and grown in LB-broth medium containing ampicilin. Test ability of the transformant in expressing lab gene was done by heating the supernatant of the transformant at 95-98Â° C for 15 minutes and determining its inhibition against Enterococcus faecalis as bacterial indicator. Location of lab gene was confirmed by analyzing recombinant plasmid and curing plasmid using acrydine orange. Analysis of the plasmid carried by transformant revealed that plasmid size was similar to that of P. acidilatici. This led to a suggestion that the plasmid was a shuttle plasmid.